Understanding the Asymmetry of Annual Streamflow Responses to Seasonal Warming in the Western United States. Issue 12 (1st December 2020) - Ban, Zhaoxin; Das, Tapash; Cayan, Dan; Xiao, Mu; Lettenmaier, Dennis P.
Abstract: The response of annual runoff volume to sub‐annual climate warming is highly uncertain, and the governing mechanisms remain poorly understood, challenging adaptive water management. A typical exemplar is the Western United States, where climate models project substantially stronger warming in the warm season (April to September) than in the cool season (October to March). We investigate the asymmetrical responses of annual and seasonal streamflow changes to warm season and cool season warming for four regionally important basins in the Western United States using an ensemble of four land surface (hydrological) models. Our results show that (i) the general features of seasonal and annual streamflow responses to asymmetrical warming are consistent across models, although the magnitudes vary. The multi‐model mean shows annual runoff declining from 2.0% up to 7.5% under 3°C warm season warming, and from 2.2% up to 4.7% under 3°C cool season warming across the four basins. (ii) The asymmetry of the seasonal evapotranspiration sensitivity to temperature constrains the asymmetry of annual streamflow responses to seasonal warming; and (iii) basins with characteristics such as high ratios of warm to cool season gross incoming water, cooler summers, and colder winters have the strongest relative annual streamflow decreases for warm season warming relative to cool season warming. The pattern in (iii) is explained by the variation of evapotranspiration‐temperature sensitivity in response to a compound set of processes, including the enhanced rate of water holding capacity increase with warmer temperatures, temperature‐related snowmelt‐albedo feedback, and enhanced surface resistance with warmer temperatures. Key Points: Streamflow responses to warm versus cool season warming for four major Western United States basins are mostly consistent across four models Evapotranspiration to temperature sensitivity dominates the asymmetry of streamflow reductions under warm versus cool season warming Differences in the basins' runoff responses to seasonal warming are mainly associated with seasonal gross incoming water and temperature